Evaluating Task Variety in an EFL Module: “Easy English for Package B (SMP)” from PKBM Bandung (Journal of Foreign Language Teaching and Learning, 2024)
English Textbook is a widely used source for teaching English in Indonesia, but studies showed that many textbook tasks are unsuitable for students’ needs. Therefore, the objective of this study was to find out the task types presented in the EFL Textbook, Easy English for Package B (Junior High School level), used by an Institution, focused on Module 1, Getting Acquaintance. The research design was a content analysis under a descriptive qualitative study. The data were collected from the EFL Module 1, and 1 teacher was recruited as a participant. The study used the task types rubric by Nunan (1999; 2004). Besides the content analysis, an interview was conducted to identify tasks found in the textbook and the teacher's perspective regarding the module. The finding showed that the module does not meet the standards of a good textbook, predominantly because it centered around linguistic tasks, comprising 97.66% of all tasks; another type of task is creative tasks, constituting only 2.32%. In other words, the module lacks diversity in task types, as there are no cognitive, interpersonal, or affective tasks. In the interview, the teacher shows a negative attitude towards the tasks in module 1, which is that the tasks ignore many other important aspects of learning. To improve, textbook makers should include various tasks from Nunan’s framework that apply to real life. Teachers should use these materials creatively, and schools should offer textbooks that provide comprehensive language tasks.